O designer ativista e seu papel na longevidade de redes de projetos para inovação social - Goldstein, Laura Folgierini (Universidade do Vale do Rio dos Sinos, 2020)
The present work presents a project journey within the Ecossistema da Moda Sustentável project, developed by a diverse group of supporters, whose purpose is to disseminate knowledge about sustainable fashion in Rio Grande do Sul. The appropriation of the method and tools of strategic design that help the activist designer in his role in project networks for social innovation. Exploration through the practice of the Ecosystem inspires a theoretical review of the themes: design for social innovation, co-design practices, ecosystems and creative communities, design guiding scenarios and, finally, the Social Innovation Journey - model of design performance in the field of social innovation, prepared by Fassi, Meroni and Simeone (2013). Such a journey presents itself as a proposal to be appropriate and redesigned for the use of the Ecossistema da Moda Sustentável, in order to meet its specific needs and help to overcome the challenges that the group encounters in its processes and in the enhancement of its actions. Practical experimentation and bibliography review point out the research problem, how to prolong the existence of design projects in the field of social innovation? The work focuses on the permanence of the designer, in his role as a social activist, as a key factor in the continuation of these social innovation projects. The Social Innovation Journey model is criticized and redesigned to meet the specific needs of the Ecossistema da Moda Sustentável. Through the production of design-oriented scenarios based on the model, they are able to facilitate dialogue and co-creation between designer and craftsman, which result not only in the extension of this project network, but also in real social innovation in the region and in the lives of the participants in situations of social vulnerability, who use handicrafts as a form of income.
Keywords: Design estratégico; Designer ativista; Ecossistemas criativos; Inovação social; Strategic design; Designer activist; Creative ecosystems; Social innovation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial